Ionic liquid-based ultrasound-assisted extraction: a novel insights of green extraction techniques for bioactive compounds from herbal plants - Aziz, Fiq'rah Lestari; Lukmanto, Donny; Iswandana, Raditya; Mu'nim, Abdul (Faculty of Pharmacy, Universitas Pancasila, 2024)
The ionic liquid-based ultrasound-assisted extraction (ILUAE) is a non-conventional environmentally friendly extraction method. ILUAE is considered as green chemistry since ILUAE utilize ionic liquids as solvents and ultrasound-assisted extraction to extract bioactive chemicals from herbal plants. The growing popularity of ILUAE as preferred extraction method in herbal medicine is not only due to its sustainable, eco-friendly characteristics but also its improvement in extraction efficiency while maintaining the quality of extracted products. Here, we discussed and reviewed ILUAE as preferred extraction method for herbal medicines. Through discussing ILUAE’s potential, advantage against traditional extraction technique, and summarized the successful extraction of bioactive components from various herbal plants using ILUAE, we hope to showcase the technology's efficiency, selectivity, and sustainability. Finally, we discussed current limitations and future challenge for ILUAE and potential ways to address these challenges.